New LISA dynamics feedback control scheme: common-mode isolation of test mass control and probes of test-mass acceleration - Inchauspé, Henri; Hewitson, Martin; Sauter, Orion; Wass, Peter (Physical review, 2022)
The Drag-Free and Attitude Control System is a central element of LISA technology, ensuring the very high dynamic stability of spacecraft and test masses required in order to reach the sensitivity that gravitational wave astronomy in space requires. Applying electrostatic forces on test masses is unavoidable but should be restricted to the minimum necessary to keep the spacecraft-test masses system in place, while granting the optimal quality of test-mass free fall. To realize this, we propose a new test-mass suspension scheme that applies forces and torques only in proportion to any differential test mass motion observed, and we demonstrate that the new scheme significantly mitigates the amount of suspension forces and torques needed to control the whole system. The mathematical method involved allows us to derive a new observable measuring the differential acceleration of test masses projected on the relevant sensitive axes, which will have important consequences for LISA data calibration, processing, and analysis.